Effects of a Novel Glucokinase Activator, HMS5552, on Glucose Metabolism in a Rat Model of Type 2 Diabetes Mellitus - Ping Wang; Huili Liu; Li Chen; Yingli Duan; Qunli Chen; Shoumin Xi (Journal of Diabetes Research)
Glucokinase (GK) plays a critical role in the control of whole-body glucose homeostasis. We investigated the possible effects of a novel glucokinase activator (GKA), HMS5552, to the GK in rats with type 2 diabetes mellitus (T2DM). Male Sprague-Dawley (SD) rats were divided into four groups: control group, diabetic group, low-dose (10 mg/kg) HMS5552-treated diabetic group (HMS-L), and high-dose (30 mg/kg) HMS5552-treated diabetic group (HMS-H). HMS5552 was administered intragastrically to the T2DM rats for one month. The levels of total cholesterol, triglyceride, fasting plasma insulin (FINS), and glucagon (FG) were determined, and an oral glucose tolerance test was performed. The expression patterns of proteins and genes associated with insulin resistance and GK activity were assayed. Compared with diabetic rats, the FINS level was significantly decreased in the HMS5552-treated diabetic rats. HMS5552 treatment significantly lowered the blood glucose levels and improved GK activity and insulin resistance. The immunohistochemistry, western blot, and semiquantitative RT-PCR results further demonstrated the effects of HMS5552 on the liver and pancreas. Our data suggest that the novel GKA, HMS5552, exerts antidiabetic effects on the liver and pancreas by improving GK activity and insulin resistance, which holds promise as a novel drug for the treatment of T2DM patients.